Study on the Adsorption Mechanism of Graphene Oxide by Calcareous Sand in South China Sea - Beifeng Lv; Wenjie Yu; Jiale Luo; Biao Qian; Mulugeta Belete Asefa; Na Li (Adsorption Science & Technology)
To remove graphene oxide from wastewater, we used batch experiments with calcareous sand to recover GO. The adsorption properties and mechanisms of GO by calcareous sand were investigated by different characterization techniques. In this paper, the relationship between the coagulation of GO on calcareous sand and pH, calcareous sand content, GO initial concentration, and temperature was studied. The results show that calcareous sand can effectively adsorb GO from aqueous solution, the interaction of GO with calcareous sand achieved interaction equilibrium in 5 h, and the adsorption of GO by calcareous sand strongly depends on pH. The isotherm data fitted to a Langmuir equation. A possible mechanism can be expressed from FT-IR, XRD, Raman spectra, SEM, EDS, TEM, AFM, and XPS results. The test results indicate that calcareous sand is a potentially recoverable GO material.